2010
DOI: 10.1017/s0317167100010829
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Familial Risk Factors of Parkinsons Disease: Case-Control Study

Abstract: Parkinson's disease (PD), a neurodegenerative disease, affects approximately 1% of the elderly population over 60 years. Prevalence of PD varies between 18 and 148 per 1,00,000 population world-wide 1 . Age-adjustment and restriction to studies using similar methodology reduce the variation between 102 and 190 per 1,00,000 population in Western countries. The Euro-Parkinson study 2 reported the prevalence rates from five European countries namely USA, Germany, France, UK and Sweden within a similar range. As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 41 publications
3
37
2
4
Order By: Relevance
“…One possibility is that the lactonase activity per se is essential for regulation of death and oxidative stress. Multiple lines of evidence have shown that environmental factors such as pesticide exposure can increase the risk of early onset of Parkinson's disease [72], [73], [74]. Paraoxon is an organophosphorus compounds, active metabolite of the insecticide parathion, whose toxicity is due to their strong anticholinesterase action.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the lactonase activity per se is essential for regulation of death and oxidative stress. Multiple lines of evidence have shown that environmental factors such as pesticide exposure can increase the risk of early onset of Parkinson's disease [72], [73], [74]. Paraoxon is an organophosphorus compounds, active metabolite of the insecticide parathion, whose toxicity is due to their strong anticholinesterase action.…”
Section: Discussionmentioning
confidence: 99%
“…Bower et al 9) studied the association of three personality traits related to neuroticism with a subsequent risk of PD. Sanyal et al 10) also reported that a previous history of depression was associated with increased risk of PD. These studies suggested that depression might predict an increased risk of PD developing many years later, and common background may exist in the etiology of both PD and depression.…”
Section: Depression and Heavy Metals In Pd Patientsmentioning
confidence: 97%
“…The study suggested that an anxious personality trait might predict an increased risk of PD developing many years later. Sanyal et al 11) also reported that the multivariate analysis revealed that a previous history of depression was associated with increased risk of PD.…”
Section: Introductionmentioning
confidence: 95%